ANALISIS HUKUM PENYALAHGUNAAN NARKOTIKA UNTUK DIRI SENDIRI - Rustama Ndruru (LPPM Universitas Nias Raya, 2026)
Narcotics are artificial substances or derived from plants that have hallucinatory effects, decrease consciousness, and cause addiction. Narcotics crime is an act that violates the law and is an organized crime, one of the narcotics crimes examined and tried by the Bengkayang District Court, namely decision number 67/Pid.Sus/2020/PN.Bek. in this decision, the perpetrator was sentenced to only 2 (two) years in prison for violating Article 127 paragraph (1) of Law number 35 of 2009 concerning narcotics. Based on the judge`s decision against the defendant, the author is interested in conducting research with the title